Women in the story of Jesus the gospels through the eyes of nineteenth-century female biblical interpreters - Weir, Heather E.; Taylor, Marion Ann (Grand Rapids, Michigan William B. Eerdmans Publishing Company, 2016)
Part 1. Heart and hands: women's spirituality -- 1. Mary: the exemplary disciple -- Clara Lucas Balfour: humility: the noblest virtue -- Elizabeth Stuart Phelps: receiving the divine -- Sarah Trimmer: blessed humility -- Gracilla Boddington: worshipping with Mary -- Mary Anne SchimmelPennick: hail her as the woman -- Elizabeth Wordsworth: Cleopatra or Mary? -- Christina Georgina Rossetti: the veiled virgin -- Elizabeth Rundle Charles: communion and sacrifice -- 2. Mary and Martha of Bethany: spirituality in the workplace -- Esther Hewlett Copley: consecrated abilities -- Clara Lucas Balfour: action and contemplation -- Nina L. McFadyen: the happy home in Bethany -- Etty Woosnam: meddlesome Matty -- M. G.: work and devotion -- Mary Ann Smith: doing what we can -- Part 2. Unsealed lips: women preaching -- 3. Anna: the vocation of a woman preacher -- Sarah Hale: Anna's spiritual superiority -- Elizabeth Baxter: a role model for female ministry -- Elizabeth Wilson: a woman with a vocation -- M. G.: A widow's vocation: a sermon -- 4. The woman at the well: the first Samaritan evangelist -- Clara Lucas Balfour: a changed woman -- Elizabeth Baxter: the gospel preacher -- Phoebe Palmer: women's preaching justified -- Hannah Jane Locker-Lampson: empathetic evangelistic preaching: a sermon -- Mary Elizabeth Beck: bearing the words of life: a sermon -- 5. Herodias and Salome: the royal tigresses judged -- Harriet Beecher Stowe: it's all about power -- Euphemia Johnson Richmond: voluptuous dancing -- Mrs. Donaldson: the great danger of worldly amusements: a sermon -- Margaret Black: pleasing the tyrant -- Part 3. Unveiled eyes: women and the biblical text -- 6. A woman of Canaan: experiencing the text -- Caroline Pridham: Gentile dogs? -- Elizabeth Rundle Charles: traveling to Tyre -- Mrs. Donaldson: dealing with our demons: a sermon -- 7. The adulterous woman: teaching troublesome texts -- Lucy Barton: heart searching -- Mary Cornwallis: we behold the woman -- Charlotte Bickersteth Wheeler: who cound invent it? -- Elizabeth Baxter: where is the man? -- Josephine Butler: the sex bias of the commentators -- 8. Mary Magdalene: receiving the text -- Anna Jameson: mythic Magdalene -- Harriet Beecher Stowe: redeemed penitent -- Charlotte Bickersteth Wheeler: carry the glad tidings -- Elizabeth Baxter: apostle of the resurrection -- Elizabeth Cady Stanton: gullible woman -- Amelia Gillespie Smyth: harmonizing Magdalene -- Elizabeth Rundle Charles: hidden depths
This volume gathers the writings of thirty-one nineteenth-century women on the stories of women in the Gospels Mary and Martha, Anna, the Samaritan woman at the well, Herodias and Salome, Mary Magdalene, and more. The selected excerpts represent various literary genres, including commentaries, Scripture biographies, essays, travel diaries, children's lessons, and sermons. Retrieving and analyzing neglected works by Christina Rossetti, Sarah Hale, Elizabeth Wordsworth, and many other nineteenth-century writers, Women in the Story of Jesus illuminates the biblical text, recovers a neglected chapter of reception history, and helps us understand and apply Scripture in our present context. - back of book
Includes bibliographical references and indexes
Keywords: Bible -- Feminist criticism; Bible; Women in the Bible; RELIGION ; Biblical Studies ; Jesus, the Gospels & Acts; RELIGION ; Biblical Studies ; New Testament; Feminist Criticism